Resistance Exercise and Whey Protein Supplementation Reduce Mechanical Allodynia and Spinal Microglia Activation After Acute Muscle Trauma in Rats - Rodrigues, Gusthavo; Moraes, Thamyris; Elisei, Lívia; Malta, Iago; dos Santos, Rafaela; Novaes, Rômulo; Lollo, Pablo; Galdino, Giovane (Frontiers in Pharmacology, 2021)
Muscle injury caused by direct trauma to the skeletal muscle is among the main musculoskeletal disorders. Non-pharmacological treatments have been effective in controlling muscle injury–induced pain; however, there are just a few studies in the literature investigating this response. Thus, the present study aimed to evaluate the effect of a resistance exercise training protocol combined or not with whey protein supplementation on mechanical allodynia induced by muscle injury. In addition, we also investigated the involvement of spinal glial cells in this process. For this purpose, male Wistar rats underwent a muscle injury model induced by direct trauma to the gastrocnemius muscle. Mechanical allodynia was measured by a digital von Frey algesimeter test. To evaluate the effect of exercise and/or supplementation on mechanical allodynia, the animals practiced exercises three times a week for 14 days and received supplementation daily for 14 days, respectively. Moreover, the effect of both the participation of spinal glial cells in the muscle injury and the resistance exercise training and/or whey protein supplementation on these cells was also investigated by the Western blot assay. The results demonstrated that resistance exercise training and whey protein supplementation, combined or alone, reduced mechanical allodynia. These treatments also reduced the number of interstitial cells and pro-inflammatory cytokine IL-6 levels in the injured muscle. It was also found that spinal microglia and astrocytes are involved in muscle injury, and that resistance exercise training combined with whey protein supplementation inhibits spinal microglia activation. The results suggest that both resistance exercise training and whey protein supplementation may be effective non-pharmacological treatments to control pain in the muscle after injury induced by acute trauma.